On the ontological Concept of Sexual Difference: A material, dynamical and synthethica Approach - Binetti, María José (2020)
Men and women are sexually different, and the differences matter. However, such differences have little to do with the dualism of gender stereotypes, the power hierarchies of patriarchy, or the biological determinism of two opposite and exclusive sexes. How to understand the sexual difference then? This paper aims at answering the question from the framework of a material realism that has overcome the dualism of difference as well as the biological reductivism of sexuality.